A Proposed Artificial Intelligence-Based System for Developing E-management Skills in Saudi Primary Schools - Hagag, Ahlam Mahmoud; Elnaggar, Mohamed Elsayed; Sharaf, Rasha Saad (European Scientific Journal, ESJ, 2023)
This study aims to investigate the impact of Artificial intelligence-driven solutions on school leaders’ proficiencies. Leaders have the responsibility of making decisions in educational institutions as well as carrying out routine tasks daily. Artificial intelligence-assisted applications have noteworthy contributions to the field of educational management. The scope of this study is limited to selected features; data analytics, chatbot, and e-survey. The basic design of this study started with analyzing literature in this domain. This was followed by designing a system consisting of four models: building a dashboard, predicting students’ results, creating a chatbot for responding to parents’ queries and creating an e-survey for measuring staff satisfaction. The participants of this study consist of 35 school leaders, whereas the sample was one group that was exposed to special treatment. A pre/post-test was conducted to examine the impact of the treatment, in addition to an observation card that was used to measure the treatment’s impact on the technical domains. The researchers used SPSS to analyze the study’s results. The prominent finding of this study is the significant impact of Artificial intelligence on leaders’ competencies; the difference between mean scores in both pre and post-test application and post-application for the observation card has proven the positive impact of the proposed treatment.